PENGARUH STRATEGI PEMBELAJARAN DISCOVERY DAN CARA BELAJAR SISWA TERHADAP KARAKTER SISWA - M. Taufiq Hidayah Tanjung; Reh Bungana Beru Perangin-angin; Dede Ruslan (JURNAL TEMATIK, 2018)
This study aims to find out the effect of discovery learning strategy and students’ learning style on students’ character.  This study use quantitative approach  with experimental quasi method.  This study is conducted in class V of SDN 064015 and SDN 0960873 in Medan City with population and sample are 120 students.  Data of study is obtained through attitude test in the form of questionnaire.  The result obtained in this study shows that there is interaction between Discovery learning strategy and students’ learning style on students’ character.  The result of interaction between learning strategy and students’ learning style in this study is 0.000 < 0.05 significantly which means that the enhancement of students’ character in experiment class is better if compared to control class.  This shows that Discovery learning strategy and students’ learning style is very influential to students’ character.